2010
DOI: 10.1175/2009mwr3031.1
|View full text |Cite
|
Sign up to set email alerts
|

The Diurnal Cycle of Winds, Rain, and Clouds over Taiwan during the Mei-Yu, Summer, and Autumn Rainfall Regimes

Abstract: The diurnal variations in surface winds, rain, and clouds over Taiwan are presented for three rainfall regimes: the mei-yu (16 May–15 June), summer (16 July–31 August), and autumn (16 September–15 October). Though the magnitude of diurnal island divergence and convergence is similar under each regime, the diurnal variations of rain and clouds vary considerably between the regimes. These differences are related to the seasonal changes in environment winds, stability, moisture, and weather systems. In addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 34 publications
4
29
0
Order By: Relevance
“…5). This is in agreement with Kerns et al (2010) that skies are generally clearer in the morning than in the afternoon. On clear mornings when the sun is able to heat the Earth's surface the conditions for cumulus formation are favorable.…”
Section: Cloud Index Statisticssupporting
confidence: 92%
“…5). This is in agreement with Kerns et al (2010) that skies are generally clearer in the morning than in the afternoon. On clear mornings when the sun is able to heat the Earth's surface the conditions for cumulus formation are favorable.…”
Section: Cloud Index Statisticssupporting
confidence: 92%
“…Among these weather systems, convective afternoon rainfall (hereafter, CAR) is the most frequently observed pattern (Wang and Chen 2008). Because of its importance to local residents, the characteristics and causes of CAR have been examined in many studies (Chen et al 1991;Johnson and Bresch 1991;Kerns et al 2010;Lin et al 2011;Huang and Chan 2012;Wang et al 2013). Studies have noted that CAR generally occurs on a day associated with a stronger sea breeze circulation during the daytime (e.g., Lin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, for all three cases studied, localized heavy rainfall occurs at night as the surface front approaches with increasing strength of the pre-frontal southwesterly monsoon flow. Previous studies have shown that orographic blocking is most pronounced at night and in the early morning when the land surface is coldest (Chen and Li 1995b;Kerns et al 2010;Lin et al 2011).…”
Section: Orographic Effects As the Low-level Trough Approaches Taiwanmentioning
confidence: 99%
“…It is well known that the interaction between the cold pool of convective cells and the environmental flow can enhance convection (Kerns et al 2010;Markowsla and Richardson 2010). At 20 LST 2 June, when the simulated precipitation system is still over the southeastern coast of China (Fig.…”
Section: The Cold Pool From Convectionmentioning
confidence: 99%
See 1 more Smart Citation